ANALYSIS OF FINANCIAL PERFORMANCE USING THE CAMEL METHOD AT PT. BANK SULSELBAR - Risa Pradista, Noviana; Darmawan Natsir, Uhud; Nurman, Nurman (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine the financial performance of PT Bank Sulselbar as measured using the CAMEL Method (Capital, Assets, Management, Earning, and Liquidity). The object of research is PT Bank Sulselbar. The type of research used is quantitative descriptive research, the type of data used is primary and secondary data, the sample used is the financial statements of PT Bank Sulselbar from 2017 to 2021. The results in this study are the financial health condition of PT. Bank Sulselbar in the 2017 and 2018 periods is in the "HEALTHY" predicate with a credit value above 81% in accordance with the provisions stipulated by Bank Indonesia, while in the period 2019 to 2021 it is in the "STRONGLY HEALTHY" predicate because the credit value is below the provisions set by Bank Indonesia. This means that PT. Bank Sulselbar shows that the financial performance using the CAMEL method is in a healthy predicate, which means that PT. Bank Sulselbar is able to manage and handle problems that arise during that period.